2015
DOI: 10.3390/ijerph120303060
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Zinc with Oxidative Stress Biomarkers

Abstract: Hypertension and smoking are related with oxidative stress (OS), which in turn reports on cellular aging. Zinc is an essential element involved in an individual’s physiology. The aim of this study was to evaluate the relation of zinc levels in serum and urine with OS and cellular aging and its effect on the development of hypertension. In a Spanish sample with 1500 individuals, subjects aged 20–59 years were selected, whose zinc intake levels fell within the recommended limits. These individuals were classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Moreover, the peak total oxidants in blood of hair fall-suffered objects could be correlated with lower levels of serum zinc that is remarkably influenced by oxidative stress. The same results were showed by Morales-Suárez-Varela et al (2015) who inspected the linkage between serum zinc and oxidative stress and measured minimal serum zinc levels respective with cellular senescence generated from oxidative exertion.…”
Section: Serum 8-oxodg (Ng/ml)supporting
confidence: 66%
See 1 more Smart Citation
“…Moreover, the peak total oxidants in blood of hair fall-suffered objects could be correlated with lower levels of serum zinc that is remarkably influenced by oxidative stress. The same results were showed by Morales-Suárez-Varela et al (2015) who inspected the linkage between serum zinc and oxidative stress and measured minimal serum zinc levels respective with cellular senescence generated from oxidative exertion.…”
Section: Serum 8-oxodg (Ng/ml)supporting
confidence: 66%
“…Murr et al (2012) indicated that the low concentration of serum zinc is usually associated with oxidative stress. Morales-Suárez-Varela et al (2015) detected the association between serum zinc and oxidative stress and revealed that the minimal serum zinc levels were strongly correlated with oxidative stress-generating cellular senescence. Mohammadi et al (2021) displayed that supplying adults with zinc created a reduction in oxidative stress and inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%
“…To add to the problem of inadequate intake, some elderly individuals have a reduced capacity to absorb or utilize zinc due to drugs or disease, which exacerbates the effects of low intakes (44). Low zinc levels in serum were correlated with oxidative stress and cellular aging (45).…”
Section: Mineral Status and Grain-based Foodsmentioning
confidence: 99%